2022 TB programme review in Pakistan: strengthening governance, with better patient diagnosis and treatment - M. van den Boom; K. Bennani; C. Sismanidis; C. Gunneberg; L. Khawaja; M.A. Safdar; C. Muhwa; E. Heldal; D.M. Cirillo; A.W. Khan; R. Fatima; B.J. Khan; et al. (IJTLD Open)
BACKGROUND: In Pakistan, 84% of healthcare is provided by the private sector. We conducted an epidemiological and programme review for TB to document progress and guide further efforts. METHODS: Surveillance and data systems were assessed before analysing epidemiological data. We reviewed the programme at federal, provincial and peripheral levels and compiled national data along with WHO estimates to describe the evolution of epidemiological and programme indicators. RESULTS: In 2021, of the estimated number of TB cases, 55% of overall cases and 18% of drug-resistant cases were diagnosed and treated respectively. The contribution of the private sector in case detection increased from 30% in 2017 to 40% by 2021. For newly diagnosed pulmonary TB cases, the overall proportion of confirmed cases was 52%. In 2021, testing for rifampicin resistance among confirmed cases was 66% for new and 84% for previously treated patients. The treatment success rate exceeded 90% for drug susceptible TB. The main challenges identified were a funding gap (60% in 2021–2023), fragmented electronic systems for data collection and suboptimal coordination among provinces. CONCLUSIONS: The main challenges prevent further progress in controlling TB. By addressing these, Pakistan could improve coverage of interventions, including diagnosis and treatment. Bacteriological confirmation using recommended diagnostics also requires further optimisation.